When Land Becomes a Burden: An Analysis of an Underperforming Zambian Land Deal. (September 2021) - Salverda, Tijo; Nkonde, Chewe
Abstract: From 2011 onward, a European agribusiness progressively purchased about 38, 000 hectares of land in Zambia. Although operations have commenced on the ground, only part of the land has been developed. Salverda and Nkonde look at the reasons for and implications of this partial development, focusing particularly on how, in such a context, Zambia's slow-moving land administration, lack of financing, and the presence of rural residents on the purchased land have become self-reinforcing challenges. Their aim is to provide insights about why (very large) land deals often fail to achieve their projected capacity, leaving both investors and local residents in limbo.